AL Ittifaq Principles In Contract Law Transcendental Philosophical Perspective - Andria Luhur Prakoso; Absori Absori (DE LEGA LATA: JURNAL ILMU HUKUM, 2022)
Contract law is part of civil law, which in fiqh is included in muamalah fiqh. This regulation regarding contact is subject to the Civil Code, which should be based on established principles. One of the principles is the principle of agreement (al ittifaq) or the principle of consensualism. This manuscript itended to explain the principle of al ittifaq (consensualism) from the perspective of transcendental philosophy. This research was a desk research, so the data source was secondary data, which was collected through identification and recording of relevant data that can be used to answer the research purposes. Data analysis using the perspective of transcendental philosophy which was based on the relationship of reason and revelation. The results showed that the principle of al ittifaq (consensualism) was the result of human thought based on the arguments of revelation as in Q.S. An Nisa /4 : 29, Q.S. Al Maidah /5 : 1, Q.S. Ali Imron/3 : 159. The result of that thought resulted in fiqh rules as contractual principles. The novelty of this research was the hybridization of the values of Islamic law into positive civil law which should be conducted to give positive law more conscientious and fair. It will reflect Pancasila values which is the source of national law